Using of Intraoperative Cell Salvage and Tranexamic Acid as Protective Factor for Postoperative Anemia Appearance in Patients with Total Hip or Knee Arthroplasty - Svetislav Matić; Mira Vuković; Aleksandar Vukićević (Surgeries, 2021)
(1) Background: The purpose of this study was to investigate intraoperative pharmacological and nonpharmacological methods and techniques in reducing blood loss in patients following total hip or knee arthroplasty. (2) Methods: A retrospective cross-sectional study was conducted in patients undergoing TKA or THA surgery, electively performed at the General Hospital Valjevo, Valjevo, Serbia, in 2014 when the principles of patient blood management (PBM) were not applied at all or in part, and in 2019 when PBM principles were applied as standard. (3) Results: This study includes 197 patients, of whom 83.8% developed postoperative anemia (PA defined by haemoglobin < 12 g/dL in both sexes). Using multivariate logistic regression and ROC curve analysis, it was shown that the use of tranexamic acid (TXA) with intraoperative cell salvage (ICS) in patients without preoperative anemia reduced the incidence of PA (odds ratio = 0.081). (4) Conclusions: Preoperative diagnosis and treatment of anemia are necessary in orthopedic patients since the use of TXA with ICS strongly reduces PA in patients without preoperative anemia.